2008
DOI: 10.1051/0004-6361:200810294
|View full text |Cite
|
Sign up to set email alerts
|

Collisional effects in the far red wing of Lyman-$\sf \alpha$

Abstract: Context. An accurate determination of the line broadening of the Lyman series of atomic hydrogen has been shown to be fundamental to interpretating UV and FUV spectra of DA white dwarfs. Quasi-molecular lines have been detected in the red wing of Lyman-α, Lyman-β, and Lyman-γ. They arise from radiative collisions of excited atomic hydrogen with unexcited neutral hydrogen atoms or protons. Aims. The aim of this paper is twofold. First, we examine the range of validity of the one-perturber approximation widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…By propagating in both directions, we were able to obtain both symmetric and broken-symmetry solutions for several of the states. The Allard-Kielkopf correlation diagram 17 was used to check the dissociation products. Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…By propagating in both directions, we were able to obtain both symmetric and broken-symmetry solutions for several of the states. The Allard-Kielkopf correlation diagram 17 was used to check the dissociation products. Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The curves for b − i and b − h transitions are visually identical. Allard & Kielkopf (2009) noted in a recent study that simultaneous collisions with more than one perturber give an additional absorption from X − B transitions. Specifically, collisions with multiple atoms yield X − B opacity contributions, which dominate the 180-300 nm region.…”
Section: R E S U Lt Smentioning
confidence: 97%
“…This tension between the Lyα line wing and the CIA absorption indicates that one or perhaps both mechanisms are responsible for the mismatch. For example, the static broadening model of Kowalski & Saumon (2006) could be improved by considering dynamic collisions (Allard & Kielkopf 2009) or more accurate potential and dipole surfaces for the H-H 2 system during a collision. Another possibility is the corresponding "Lyα" absorption from a H 2 molecule between its electronic ground state and its first electronic excited state, which is not accounted for in the Kowalski & Saumon (2006) model.…”
Section: Discussionmentioning
confidence: 99%
“…Collisions of neutral H atoms with H, He and H 2 were modeled and Kowalski & Saumon (2006) showed that in very cool white dwarfs the broadening of Lyα was caused primarily by collisions with H 2 molecules. Subsequently, Allard & Kielkopf (2009) computed Lyα profiles broadened by collisions with H and He but not H 2 . As a result of this omission, their profiles do not extend into the optical and are unable to fully explain the flux deficiency observed in very cool WDs.…”
Section: Introductionmentioning
confidence: 99%